Blueshift of optical band gap in ZnO thin films grown by metal-organic chemical-vapor deposition - Chen, B. J. (2013)
The optical band gap of ZnO thin films deposited on fused quartz by metal-organic chemical-vapor deposition was studied. The optical band gap of as-grown ZnO blueshifted from 3.13 to 4.06 eV as the growth temperature decreased from 500 to 200 °C. After annealing, the optical band gap shifted back to the single-crystal value. All the ZnO thin films studied show strong band-edge photoluminescence. X-ray diffraction measurements showed that samples deposited at low temperatures <450 °C> consisted of amorphous and crystalline phases. The redshift of the optical band gap back to the original position after annealing was strong evidence that the blueshift was due to an amorphous phase. The unshifted photoluminescence spectra indicated that the luminescence was due to the crystalline phase of ZnO, which was in the form of nanocrystals embedded in the amorphous phase.